2013
DOI: 10.1002/chir.22223
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Enantiomers of RC-33 as Neuroprotective Agents: Isolation, Configurational Assignment, and Preliminary Biological Profile

Abstract: In this study we addressed the role of chirality in the biological activity of RC-33, recently studied by us in its racemic form. An asymmetric synthesis procedure was the first experiment, leading to the desired enantioenriched RC-33 but with an enantiomeric excess (ee) not good enough for supporting the in vitro investigation. An enantioselective high-performance liquid chromatography (HPLC) procedure was then successfully carried out, yielding both RC-33 enantiomers in amounts and optical purity suitable fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 32 publications
3
28
0
Order By: Relevance
“…Moreover, the design of the experiments took into account the good solubility of 1 , 2 , 3 in alcohols. For this reason the first set of experiments was performed on the considered columns, eluting with just methanol …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, the design of the experiments took into account the good solubility of 1 , 2 , 3 in alcohols. For this reason the first set of experiments was performed on the considered columns, eluting with just methanol …”
Section: Resultsmentioning
confidence: 99%
“…For this reason the first set of experiments was performed on the considered columns, eluting with just methanol. 14 As a result of a first screening with pure methanol, it was found that Chiralcel OJ-H (4.6 mm × 150 mm, 5 μm) lead to relatively short retention times, high enantioselectivity, and high resolution for compound 2 (α = 3.3, R s = 6.7) and 3 (α = 1.9, R s = 4.1). Accordingly, these experimental conditions were selected for the scale-up to (semi)-preparative scale.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, accumulating evidence highlighted the potential role of S1R agonists in exerting neuroprotective and/or restorative effects, by reducing excitotoxicity and oxidative damage [7][8][9][10][11]. Along the years, Rossi et al designed and synthetized a S1R modulator compound library, belonging to the common arylalkyl(alkenyl) aminic scaffold, which led the identification of 1-[3-(1,1 -biphen)-4-yl]butylpiperidine (henceforth , as a molecule endowed with the most promising pharmacological profile and able in promoting nerve growth factor(NGF)-induced neurite outgrowth in PC-12 cells [12][13][14][15]. In the light of these properties, RC-33 was selected as a neuroprotective agent to further investigate the role of S1R agonists in treating SCI.…”
Section: Introductionmentioning
confidence: 99%